PSXVI-9 An Analysis of Horse Related Injuries. (7th December 2018) - Camargo, F; Lawyer, K; Pollack, S; Mattingly, F; Cooper, T; Gombeski, W
Abstract: Horseback riding is a rewarding and thrilling sport and recreational activity. However, it does not come without risks. A high percentage of riders will experience some sort of injury, with different degrees of severity, throughout their riding careers. In an attempt to direct educational efforts for injury prevention while around horses, a deeper understanding of the types of injuries, and what causes people to be admitted to the hospital, are needed. This study looked at 2017 horse-related injuries data from the University of Kentucky Albert B. Chandler Hospital. Out of 251 total patients, 191 were treated in the Emergency Department and released, and 60 were admitted to the hospital. The study population consisted of the 60 admitted patients. These numbers indicate that the admission rate to UK Hospital is 23.9% for horse-related injuries. The age of all patients ranged from 1 to 75 years of age, 147 were female and 104 were male. There was no significant difference between gender in this population. The population was divided by age groups (children: 0–12; Teenagers: 13–19; Young Adults (20–35); Adults (36–55); Seniors (>56). The admittance rate was higher in children and seniors (p<0.05). The mean hospital cost was higher in seniors (p<0.05). Although there was no significant difference between age groups regarding the body region injured, the regions that were most frequently affected were thorax and abdomen, and limbs (p<0.05). The majority of injuries were the result of a fall (p<0.05). This data does not diminish the concern for head trauma as we assume that the majority of concussions did not result in admission to the hospital. However, it does indicate areas that need to be addressed with education and injury prevention methods that may have been previously overlooked, and provides data to make a case for the importance of horse safety.